Racial violence on trial - Waldrep, Christopher (Oxford, 2001)
This book looks at the history of efforts to use law to combat racial prejudice and hate in the United States. Charles Hamilton Houston, the great black lawyer, called the use of law to correct social wrongs "social engineering."
Keywords: Trials(hate crimes)-United states